Structural characterization and optical properties of light-emitting poly(9,9-didecylfluorenyl-2,7-vinylene) (PFV) generated via horner-emmons polycondensation - Philaiwan Aiamsen (2018)
This paper describes a simple strategy for preparing light-emitting poly(9,9-didecylfluorenyl-2,7-vinylene) (PFV) by Horner-Emmons polymerization using aromatic dialdehydes and diphosphonates as monomers in the presence of potassium reri-butoxide. The Horner-Emmons polycondensation gave samples of PFV with moderate molecular weights and no detectable saturated defects along the conjugated backbone. The samples of PFV were readily soluble in common organic solvents due to the presence of the flexible alkyl side chains at the C-9 position of the fluorene unit. The structure and optical properties of the PFVs were characterized by gel permeation chromatography (GPC), NMR spectroscopy, UV-vis spectroscopy, and fluorescence spectroscopy. ©2008CPST.